Labour force participation of the elderly in Europe: the importance of being healthy - Kalwij, Adriaan S.; Vermeulen, Frederic (Bonn, 2005)
"In this paper we study labour force participation behaviour of individuals aged 50-64 in 11 European countries. The data are drawn from the new Survey of Health, Ageing and Retirement in Europe (SHARE). The empirical analysis shows that health is multi-dimensional, in the sense that different health indicators have their own significant impact on individuals' participation decisions. Health effects differ markedly between countries. A counterfactual exercise shows that improved health conditions may yield over 10 percentage points higher participation rates for men in countries like Austria, Germany and Spain, and for females in the Netherlands and Sweden. Moreover, we show that the declining health condition with age accounts considerably for the decline in participation rates with age."